Impact of Green Sukuk, Green Disclosure, and ESG on Financial Performance - Shafira Azzahra Ramadhani; Yusmaniarti Yusmaniarti (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This study examines the effects of green sukuk, green disclosure, and environmental, social, and governance (ESG) performance on financial performance among Jakarta Islamic Index (JII) listed companies during 2021–2024. Employing a quantitative associative design, it utilizes secondary data from annual and sustainability reports. Purposive sampling yielded 20 firms, resulting in 80 observations overall. Panel data regression analysis was performed using EViews 12 software. The findings reveal a negative effect of green sukuk on financial performance, whereas green disclosure and ESG performance exhibit no significant impact. These findings indicate that the implementation of green financial instruments and sustainability practices has not yet had a direct positive impact on corporate financial performance in the short term, due to implementation costs and the need for long-term economic benefits. This study is expected to contribute empirical evidence to the literature on Islamic finance and sustainable finance.